SHARI’AH ORIENTED PUBLIC POLICY ON ACEH EXPENDITURE AND DEVELOPMENT - Muhammad Dayyan (IAIN Langsa, 2016)
his paper propuses Aceh public expenditure policy in economic developmentespecially in the area of an improvement in the living conditions of the majority of anation‟s citizens- not only in their physical well-being but also improvements insuch aspects as their spiritual life, general happiness, right to be free, and the rightand ability to enjoy the beauties of nature. We argue based on shari’ah oriented thatpublic expenditure accelerates economic development by giving priorities topreserve the necessary interest that are preserved ad-dien (religion), an-nafs (life orself), al-‘aqal (intellect), an-nasb (family or progeny) and al-maal (property orwealth), the government will create a healthy conditions or environment foreconomic activities to achieve Islamic development goals in Aceh Province.